Using English Movies to Improve Students' Listening Skills (NOBEL: Journal of Literature and Language Teaching, 2023)
Language learning nowadays depends on the advancement of facilities and technology. Using appropriate learning media is essential to engage students in the learning process. Therefore, using English movies to improve students’ listening is not new. Previous studies about listening and using movies discussed the related impact of both topics. However, there has not been a study that focused on students’ listening difficulties, students’ experience of watching English movies, and the impacts of using English movies on students’ listening skills. This article analyzes those main topics to find the implications of using English movies for language learning improvement. This study utilizes qualitative methods with coding thematic analysis techniques to explain the interview results. The main result of the study is that students find problems during listening activities, but they can overcome those problems with several strategies. Moreover, using English movies for language learning is effective, especially for improving listening. Finally, this study was conducted to give insights about the positive impacts of using English movies for listening activities.